Keterbatasan Mobilitas sebagai Prediktor Perubahan Body Image pada Pasien Pasca Stroke - Rahayu, Sri; Sucipto, Ade; Nismawardah, Nismawardah (Jurnal Borneo Cendekia, 2025)
Background: Stroke is a leading cause of disability that results in mobility limitations and physical changes in patients. Mobility limitations experienced by post-stroke patients not only affect physical functioning but also have psychological impacts, one of which is changes in body image. Altered body perception can influence the adaptation process and quality of life of post-stroke patients. Objective: This study aimed to analyze mobility limitation as a predictor of body image changes in post-stroke patients. Methods: This study employed a quantitative analytic design with a cross-sectional approach. The study population consisted of post-stroke patients at Sultan Imanuddin Regional General Hospital, Pangkalan Bun. A purposive sampling technique was used, involving 30 respondents who met the inclusion criteria. Mobility limitation was measured using the Barthel Index, while body image changes were assessed using the Body Image Scale (BIS). Data analysis included univariate and bivariate analyses, as well as regression analysis to determine the role of mobility limitation as a predictor of body image changes. Results: The results showed that mobility limitation was significantly associated with body image changes in post-stroke patients. Higher levels of mobility limitation were associated with greater body image disturbance. Regression analysis indicated that mobility limitation played a predictive role in body image changes among post-stroke patients. Conclusion: Mobility limitation is a predictor of body image changes in post-stroke patients. Therefore, nursing interventions should focus not only on improving physical mobility but also on providing psychological support to help patients adapt to the physical changes they experience.